The Effect of Work Environment and Job Satisfaction on Employee Performance: A Quantitative Study at Bank Sulselbar - Aliya Maharani; S. Saharuddin; J. Junaidi (Golden Ratio of Mapping Idea and Literature Format, 2026)
This study examines the effects of the work environment and job satisfaction on employee performance in the banking sector, with evidence from Bank Sulselbar. A quantitative, cross-sectional design was employed using survey data collected from 36 employees through a saturated sampling technique. Data were analyzed using multiple linear regression. The findings indicate that job satisfaction exerts a positive and statistically significant effect on employee performance, suggesting that higher levels of satisfaction are associated with improved work outcomes. In contrast, the work environment demonstrates a positive but statistically insignificant effect, implying a limited direct contribution in this context. However, the joint effect of the work environment and job satisfaction is statistically significant, highlighting their combined role in shaping employee performance. This study contributes to the human resource management literature by providing empirical evidence from a regional banking context, emphasizing the dominant role of job satisfaction in driving performance. The findings indicate that job satisfaction has a positive and statistically significant effect on employee performance. In contrast, the work environment has a positive but not statistically significant effect. However, both variables simultaneously have a significant influence on employee performance.